Commentary. Archeology to Bowman’s thought, rethinking Geography and Geopolitics from and to Peru - Delgado Estrada, Juan Manuel (2021)
When we set out to carry out the first work of the classics section of this magazine on Isaiah Bowman, we not only found his production on political and geopolitical geography but also on physical geography, and much about Peru in its southern territories that we did not know. We decided to get to know Isaiah Bowman more not only as an academic but also as a politician and advisor to the highest echelons of American power in the two world wars, Bowman was convinced that he represented the free world and that is why he sadly confronted the school in his texts German geopolitics, but also in Peru in his works he describes the oppression of the Andean and Amazonian Indians who were exploited in almost slavery regimes in the south of Peru, which he detailed and was a great contribution to know the reality of Peru.But in that archeology of Bowman’s geographical thought we also find as the great architect of Latin American studies from the academic and political organizations created to study the social subject that is south of the Rio Bravo in Mexico or the Rio Grande in the United States. An artifact of that hegemonic moment of the 20th century from Washington is the project of the Map to the Millionth of Hispano America, which began the use of new cartographic techniques to collect geoinformation for that purpose.